2019
DOI: 10.1177/1129729819892796
|View full text |Cite
|
Sign up to set email alerts
|

Early cannulation of percutaneously created arteriovenous hemodialysis fistulae

Abstract: Introduction: The optimal vascular access for most dialysis patients is an arteriovenous fistula and the recognized appropriate process of care for the chronic kidney disease patient is to have the access in place ready for use when renal replacement therapy is required. Unfortunately, as a result of multiple barriers, most patients start dialysis with a catheter and many experience multiple interventions. The recent advent of the percutaneous arteriovenous fistula may offer at least a partial solution to thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The level of access blood flow obtained immediately following access creation has made early cannulation of the enAVF possible. In a study of 14 cases in which early cannulation was necessitated in order to either avoid catheter insertion or catheter exchange, 45 the time to first cannulation ranged from 1 to 12 days with a mean of 8 days. In six cases, time to first cannulation was 7 days or less.…”
Section: Discussionmentioning
confidence: 99%
“…The level of access blood flow obtained immediately following access creation has made early cannulation of the enAVF possible. In a study of 14 cases in which early cannulation was necessitated in order to either avoid catheter insertion or catheter exchange, 45 the time to first cannulation ranged from 1 to 12 days with a mean of 8 days. In six cases, time to first cannulation was 7 days or less.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Ellipsys pivotal trial suggested better results with balloon angioplasty of the anastomosis and perforating vein immediately after fistula creation to treat spasm. Subsequent studies (11,12,(14)(15)(16) performing balloon angioplasty as part of the index procedure reported decreasing the early thrombosis rate from 12% to 3%, reducing the number of maturation procedures from 2 per patient to <1, and reducing the time to maturation using the original definition from the pivotal trial from a mean of 62 days to 11 days. The authors now consider the Kidney Health Initiative guideline of a target vein flow of ≥500 mL/min and diameter of ≥5 mm as a more appropriate proxy for physiologic fistula maturation (2).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, successful 2-needle cannulation was achieved at 10-day post-creation to avoid CVC placement (19). In addition, a recent study reported 14 patients were able to initiate early dialysis with a range of 1-12 days post-endoAVF creation, and a mean time-to-dialysis of 8 days (34). Although authors did not explore the difference between early and late cannulation cohorts, the results demonstrated that early cannulation may be feasible in selected patients.…”
Section: Specific Clinical Applicationsmentioning
confidence: 99%